ISLAM DAN KAUM MINORITAS DI INDONESIA - Ahmad Yasir Huda; Ahmadiono . (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
Several definitions of minority and minority perspectives are offered by experts in Indonesia. Experts appointed by Komnas HAM RI carefully categorize minorities into five types based on ethnicity, religion and belief, disability, race and gender and sexual orientation according to socio-cultural conditions in Indonesia. Discrimination is an example of a case of the existence of a minority and a majority. Even though Indonesia regulates protection for all its citizens in accordance with the mandate of the 1945 Constitution. In addition, this paper describes the implications of Muslims if they become the majority nationally and regionally minorities in Indonesia. This description both explicitly describes the position of the majority of Muslims in Indonesia in accordance with the teachings of the Qur'an which spreads my love for all people so as to maintain peace in Indonesia. The picture is a bit contradictory if the position of Muslims is as a minority, there will be limitations to both the resources and the opportunities obtained. Therefore, it is necessary to look at the problems of minorities in Indonesia from various sides so that there is no stigma that the source of the conflict comes from religion.